«It seems that we grow younger generation “oblivious of gens”…» - A. M. Plekhanov (Омский научный вестник: Серия "Общество. История. Современность")
Alexander Mikhailovich Plekhanov is a Ph.D in history, professor, full member of the International Informatization Academy, veteran of the KGB of the USSR, retired colonel, author of several monographs devoted to the biography of F. E. Dzerzhinsky, the history of Russian secret services, defense and protection of the state border and the history of Cossacks. He is a founder of the Society for the Study of the History of Russian Secret Services and a founder of the conference «Historical Readings at the Lubyanka». This interview was given by A. M. Plekhanov during his participation in the International research and practice conference «The Activities of Russian Secret Services in the Age of Social Cataclysms», which held in Omsk on November 23rd 2017 and edited in Moscow on January 2018. It is devoted to the current state and prospects of studying the history of Russia’s secret services